2008
DOI: 10.1073/pnas.0708159105
|View full text |Cite
|
Sign up to set email alerts
|

Rapid depletion of genotypes with fast growth and bold personality traits from harvested fish populations

Abstract: The possibility for fishery-induced evolution of life history traits is an important but unresolved issue for exploited fish populations. Because fisheries tend to select and remove the largest individuals, there is the evolutionary potential for lasting effects on fish production and productivity. Size selection represents an indirect mechanism of selection against rapid growth rate, because individual fish may be large because of rapid growth or because of slow growth but old age. The possibility for direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
396
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(423 citation statements)
references
References 26 publications
(47 reference statements)
15
396
4
Order By: Relevance
“…Selection on growth rate via behaviour can occur, because fast-growing individuals tend to be more active, bold and voracious [10,11], and so, in turn, we should expect fast-growers to be more vulnerable to harvest owing to greater encounter rates with fishing gear, and lower gear avoidance. Indeed, at the group level, faster growth is associated with greater catchability, even in the absence of size selection [9,12]. In addition, several recent studies have shown biases towards more active and bold individuals in the catch [7,9,13 -15], but see [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection on growth rate via behaviour can occur, because fast-growing individuals tend to be more active, bold and voracious [10,11], and so, in turn, we should expect fast-growers to be more vulnerable to harvest owing to greater encounter rates with fishing gear, and lower gear avoidance. Indeed, at the group level, faster growth is associated with greater catchability, even in the absence of size selection [9,12]. In addition, several recent studies have shown biases towards more active and bold individuals in the catch [7,9,13 -15], but see [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, one recent study highlighted how fishing may select on life-history traits via a behavioural mechanism, even in the absence of any size selection [9]. Selection on growth rate via behaviour can occur, because fast-growing individuals tend to be more active, bold and voracious [10,11], and so, in turn, we should expect fast-growers to be more vulnerable to harvest owing to greater encounter rates with fishing gear, and lower gear avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…When harvesting is intensive, the evolutionary change to smaller size at maturity can be observed over decades [2,7] and under artificial experimental conditions can be forced to appear in just a few generations [8,9]. By contrast, low-intensity subsistence (artisanal) harvesting is widely presumed to lack sufficient directional selection to have an analogous significant evolutionary impact (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural responses may vary between and within taxa; recent research has linked intraspecific variation in prey vulnerability and defensive behaviour to behavioural syndromes (Sih et al, 2004). Boldness may be responsible for differential mortality as bold individual are more likely to take risks during foraging and dispersal and hence have higher mortality (Biro and Post, 2008;Pruitt et al, 2012).…”
Section: Prey Vulnerability Traitsmentioning
confidence: 99%